Tilted versus axial implant distribution in the posterior edentulous maxilla: A CBCT analysis. Issue 11 (23rd August 2021) - Hamilton, Adam; Jamjoom, Faris Z.; Alnasser, Muhsen; Starr, Jacqueline R.; Friedland, Bernard; Gallucci, German O.
Abstract: Objectives: This study aimed to determine whether distally angulating an implant is a successful strategy to avoid the maxillary sinus and the need for bone augmentation, while increasing the anterior‐posterior (A‐P) implant distribution in the edentulous maxilla. Materials and Methods: In 115 patients with edentulous maxillae, virtual implant planning was performed utilizing cone‐beam computer tomographs. Axial (8 mm length) and tilted (12 mm length) dental implants with 30‐degree and 45‐degree angulation were virtually positioned to avoid entering the maxillary sinus, while maximizing A‐P distribution. Measurements were made between the tilted and axial implants to assess the change in A‐P distribution of implants at the implant and abutment levels. Results: Forty‐seven sites (20.4%) were not able to have either treatment modality with insufficient bone for implant placement. Axial implants were placed more distally than 45‐degree and 30‐degree tilted implants in 24% and 42% of sites, respectively. The average change in A‐P spread measured at the implant level, for 30‐ and 45‐degree tilted implants was −0.25 mm (95% CI −0.76, 0.26) and 1.9 mm (95% CI 1.4, 2.3), respectively. When measured from the center of each multi‐unit abutment the average increase in A‐P distances for tilted implants appears larger in the 30‐degree and 45‐degree groups by 0.97 mm and 1.74 mm, respectively compared to measurements at the implant level. Conclusions: Angulating 12 mm implants provides a limited increase in A‐P distribution of implants in edentulous rehabilitation in most situations. In certain patients, the use of 8mm axial implants may provide a greater A‐P spread.